The Nutritional Risk Screening 2002 tool for detecting malnutrition risk in hospitalised patients: Perspective from a developing country - Gökcan, Hale; Selçuk, Haldun; Töre, Emin; Gülseren, Pınar; Cambaz, Hatice; Sarıtaş, Şeniz; Öcal, Ruhsen; Başaran, Özgür; Yılmaz, Uğur; Akın, Ebru (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To verify the validity of the Nutritional Risk Screening (NRS) 2002 test in a Turkish population. Materials and Methods: We prospectively investigated 2566 patients at a tertiary referral hospital. Nutritional status was screened using NRS 2002, and the length of the stay (LOS) was the main outcome measure. Hospital stays >10 days were accepted as prolonged LOS. NRS scores ≥3 were accepted as indicating risk for malnutrition. Statistical analyses were performed to determine the independent risk factors for malnutrition risk and prolonged LOS. Results: The mean age of patients was 56.6±16.9 years. According to the NRS 2002, 964 patients (37.6%) were without risk, 1320 (51.4%) warranted surveillance and 282 (11%) were at high risk for malnutrition. Malnutrition rate was the highest in the intensive care unit (22.01%). Prolonged LOS was seen in 24.4% of patients. Intensive care unit stay [odds ratio (OR): 0.585; confidence interval (CI): 1.45-2.22; p<0.001] and an NRS score ≥3 (OR: 0.88; CI: 1.87-3.13; p<0.001) were independent risk factors for prolonged LOS. Conclusion: Improving healthcare outcomes while avoiding preventable healthcare costs is an important goal of healthcare provision in developing countries. NRS 2002 was predictive of LOS, and thus, of patient prognosis. Further community-based studies are warranted to assess the impact of NRS 2002 on reducing healthcare costs.